Caracterización del perfil Hematológico y Bioquímico del Ovino Criollo Ecuatoriano en la Provincia de Cotopaxi. - Tarco Maigua, Lissette Estefania (2018)
The creole ovine is a small animal, rustic little productive and easy adaptability to the habitat with characteristics of great value for small producers. The present research has been made in the cantons of Pujilí and Saquisilí located in the Cotopaxi province, where a population of 30 selected Creole ovine was studied in the communities of Guayama, Jatumpamba, Chami, Michacalá, Cruscucho, Troya and Fucungo. The objective of the research was to characterize the hematological and biochemical profile of the creole Ecuadorian ovine in the Cotopaxi province selecting sheep with their own characteristics to be Creole. The methodology consisted of locating the places with the largest population of Creole sheep in the Cotopaxi province, blood samples were taken through an adequate subjection of the animal and puncture technique of the jugular vein depositing the samples in vacutainer tubes with and without anticoagulant thus identifying the sample for its respective transport to the San Francisco Clinical Laboratory. Through of the laboratory examinations, there were established the referential values of the variables of the hemogram and blood biochemistry for the analysis of the data the descriptive statistics was developed in Excel and the analysis of variance establishing the Tukey test the 5 % through the statistical program Infostad. The results show that the values of the hemogram and blood biochemistry of the Creoles sheep are in the normal parameters according with the referential values of said authors. The values between males and females statistically have no significance, describing that sex does not influence the values of males and females. It was presented significance in the variable of platelets this can be by physiological conditions, environmental changes or feeding.